Pemberdayaan Masyarakat dalam Pengelolaan Sampah Berbasis Ecovillage - Wulan, Sri Ratna (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Household waste management remains a significant environmental issue in Indonesia, particularly in rural areas. Limited treatment facilities and low public awareness have led most waste to be burned or disposed of without sorting, causing impacts on health and environmental quality. This study aimed to empower local residents through basic education on waste management using the ecovillage approach. The activities were conducted through participatory methods, including preliminary surveys, educational sessions, composting practices, interactive discussions, and evaluations. The results showed an improvement in community knowledge and skills in waste separation and household-scale composting. In addition, local initiatives emerged such as the formation of environmental cadres and waste banks as part of strengthening community institutions. These findings demonstrate that participatory education effectively drives behavioral change and supports the realization of environmentally sustainable villages.